2012
DOI: 10.1094/mpmi-09-11-0254
|View full text |Cite
|
Sign up to set email alerts
|

Sugarwin: A Sugarcane Insect-Induced Gene with Antipathogenic Activity

Abstract: In sugarcane fields, colonization of the stalk by opportunistic fungi usually occurs after the caterpillar Diatraea saccharalis attacks the sugarcane plant. Plants respond to insect attack by inducing and accumulating a large set of defense proteins. Two homologues of a barley wound-inducible protein (BARWIN), sugarcane wound-inducible proteins SUGARWIN1 and SUGARWIN2, have been identified in sugarcane by an in silico analysis. Antifungal properties have been described for a number of BARWIN homologues. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 56 publications
3
67
0
7
Order By: Relevance
“…According to Medeiros et al (2012), increased gene expression of the protease inhibitor protein in sugarcane observed in response to attacks by Diatraea saccharalis, was associated with injury caused by this caterpillar. Another study reported that accumulation of this protein in corn was related to mechanical damage (Tamayo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…According to Medeiros et al (2012), increased gene expression of the protease inhibitor protein in sugarcane observed in response to attacks by Diatraea saccharalis, was associated with injury caused by this caterpillar. Another study reported that accumulation of this protein in corn was related to mechanical damage (Tamayo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…coeruleum (Que et al , 2014). Moreover, sugarcane chitinases showed action against C. falcatum and are also associated with Pseudomonas -mediated induced resistance (Viswanathan et al , 2003) and with sugarcane response to D. saccharalis attack (Medeiros et al ., 2012). …”
Section: Pr Families and Their Sugarcane Homologsmentioning
confidence: 99%
“…Sugarcane has two homologs (SUGARWIN1 and SUGARWIN2) of the antifungal barley wound-inducible protein BARWIN, a class II chitinase (PR-4 family) (Medeiros et al , 2012). BARWIN is a basic protein composed of 125 residues, with the tridimensional structure stabilized by three disulfide bonds (Ludvigsen and Poulsen, 1992; Svensson et al ., 1992).…”
Section: Pr Families and Their Sugarcane Homologsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two homologues of a Barwin were identified in sugarcane by in silico analysis and were designated Sugarwin-1 and Sugarwin-2 (Medeiros et al 2012). The induction of Sugarwin transcripts occurred in response to mechanical wounding and to feeding by the sugarcane stalk borer Diatraea saccharalis.…”
Section: Prmentioning
confidence: 99%